IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI RELIGIUS HASIL BELAJAR SISWA - Abdul Hafidz; Baharuddin Baharuddin (LPPM Universitas Islam 45, 2023)
This research aims to analyze the implementation of PAI learning in instilling the habit of religious values and student learning outcomes at SMPIT Al 'Imaroh, the learning outcomes of implementing PAI learning in instilling the habit of religious values and student learning outcomes and knowing the supporting and inhibiting factors in the learning implementation process PAI in instilling religious values and student learning outcomes. The research method uses a qualitative descriptive analysis approach. Data was collected through documentation, observation and interview techniques. Data analysis applies the data triangulation method to check the validity of the data. The research results show the implementation of Islamic education learning in instilling religious values and student learning outcomes through planning aspects in the form of syllabus and lesson plans, implementation through intracurricular and extracurricular activities, and evaluation through authentic assessment, assessment of reference criteria, and reporting of learning outcomes. Learning outcomes in instilling religious values and student learning outcomes are cognitive aspects, affective aspects and psychomotor aspects. The supporting factors for the implementation of PAI learning in instilling the habit of religious values and student learning outcomes at SMPIT Al 'Imaroh are the role of the principal and all teachers of SMPIT Al 'Imaroh, the habit of 3S for students, the habit of praying in congregation and other Islamic activities, loudspeakers in schools, classrooms equipped with projectors and Al-Qur'an, libraries, prayer rooms and periodic evaluations. The inhibiting factors include the diversity of student and parent backgrounds as well as supervision of students outside of school.